Reestructuración técnico administrativa en la empresa Incarpas LTDA. (2018)
The present project was carried out with the objective of developing a restructuring administrative technician in the company Incarpas LTDA., to identify the flaws of their current state and to be able to design strategies that help to improve operational process, administrative and positioning in the market, increasing the quality of service. An external diagnosis of the sector was made using the analysis tool PESTAL, then complemented with the self-diagnostic tool of the Chamber of Commerce of Bogotá and a SWOT analysis was developed, where They related the aspects of greatest impact that affect the organization. Subsequently, the technical study was carried out in which a study of times applying method engineering tools, identifying certain inconveniences in the flow of materials and information evidenced in the management of each activity. In the administrative study, a new strategic plan for the company was designed, that allowed to improve the communication channels and the order of the processes according to the established hierarchies and the objectives set. Lastly, the financial study for I LTDA was carried out, taking into account the proposals for technical and administrative improvements, achieving a decrease in costs and expenses of $ 142,822,542 for the next 5 years, the proposed restructuring being viable, with an investment of $ 9,162,000.